Design of a Vlasov mode converter of 263 GHz gyrotron oscillator for DNP‐NMR. Issue 14 (13th June 2018) - Li, Zhiliang; Feng, Jinjun
Abstract : This paper presents design and simulation of a quasi‐optical mode converter of 263 GHz gyrotron oscillator operating in the circular TE03 mode for dynamic nuclear polarisation enhanced nuclear magnetic resonance (DNP‐NMR). The converter consists of a Vlasov stepped‐cut launcher, and additional wave beam‐shaping reflectors, including an elliptical reflector and a parabolic reflector. First, the preliminary parameters of the launcher are designed with the geometric optics theory. Next, both geometric optics and vector diffraction theory are used to simulate the propagation of wave beam in the mode converter system. Finally, operation of the mode converter was simulated, based on the physical model of Vlasov mode converter for 263 GHz TE03 mode gyrotron oscillator. The simulated results show that a good fundamental Gaussian mode is converted at the output window from the TE03 mode, and that the power conversion efficiency and the vector correlation are 90.11 and 85.23%, respectively.